Managers’Approach to the Problems of Public Library: Ankara Example - Bülent Yılmaz (Türk Kütüphaneciliği)
The main aim of this research is to investigate the current problems of the public libraries in Ankara, capital of Turkey, in the frame of their managers’ approaches in May 2000. At the end of the research which included the fifteen public libraries in eight central districts in Ankara it has been understood that the “classical” problems concerning with personnel, collection, building, budget and services are still continuing.